Lower Rate of Daily Smokers With Symptomatic COVID-19: A Monocentric Self-Report of Smoking Habit Study - Miyara, Makoto; Tubach, Florence; Pourcher, Valérie; Morélot-Panzini, Capucine; Pernet, Julie; Haroche, Julien; Lebbah, Said; Morawiec, Elise; Gorochov, Guy; Caumes, Eric; Hausfater, Pierre; Combes, Alain; et al. (Frontiers in Medicine, 2022)
Background: Identification of prognostic factors in COVID-19 remains a global challenge. The role of smoking is still controversial. Methods: Symptomatic COVID-19-PCR positive in-and outpatients from a large French university hospital were systematically interviewed for their smoking status, use of e-cigarette and nicotinic substitutes. The rates of daily smokers in in-and outpatients were compared using the same smoking habit questionnaire to those in the 2019 French general population, after standardization for sex and age. Results: The inpatient group was composed of 340 patients, median age 66 years: 203 men (59.7%) and 137 women (40.3%), median age for both 66 years, with a daily smokers rate of 4.1 % (CI 95% [2.3 – 6.9]) (5.4% of men, 2.2% of women). The outpatient group was composed of 139 patients, median age 44 years: 62 men (44.6%, median age 43 years), and 77 women (55.4%, median age 44 years). The daily smoker rate was 6.1 % (CI 95% [2.7 - 11.6]) (5.1% of men, 6.8% of women). Among inpatients, daily smokers represented 2.2% and 3.4% of the 45 dead patients and of the 29 patients transferred to ICU, respectively. The rate of daily smokers was significantly lower in COVID-19 patients, as compared to that in the French general population after standardization by age and sex, with Standardized Incidence Ratios of 0.24 [0.12 - 0.48] for outpatients and 0.24 [0.14 - 0.40] for inpatients. Conclusions: Daily smoker rate in patients with symptomatic COVID-19 is lower as compared to the French general population